Balanced Rac1 and RhoA activities regulate cell shape and drive invagination morphogenesis in epithelia - Chauhan, Bharesh K. (National Academy of Sciences, 2011)
Epithelial bending is a central feature of morphogenesis in animals. Here we show that mutual antagonism by the small Rho GTPases Rac1 and RhoA determines cell shape, tissue curvature, and invagination activity in the model epithelium of the developing mouse lens. The epithelial cells of the invaginating lens placode normally elongate and change from a cylindrical to an apically constricted, conical shape. RhoA mutant lens placode cells are both longer and less apically constricted than control cells, thereby reducing epithelial curvature and invagination. By contrast, Rac1 mutant lens placode cells are shorter and more apically restricted than controls, resulting in increased epithelial curvature and precocious lens vesicle closure. Quantification of RhoA- and Rac1-dependent pathway markers over the apical–basal axis of lens pit cells showed that in RhoA mutant epithelial cells there was a Rac1 pathway gain of function and vice versa. These findings suggest that mutual antagonism produces balanced activities of RhoA-generated apical constriction and Rac1-dependent cell elongation that controls cell shape and thus curvature of the invaginating epithelium. The ubiquity of the Rho family GTPases suggests that these mechanisms are likely to apply generally where epithelial morphogenesis occurs.